Extensive Tracking Performance Analysis of Classical feedback control for XY Stage ballscrew drive system - ABDULLAH, LOKMAN; JAMALUDIN, ZAMBERI; RAFAN, NUR AIDAWATY; YAAKOB, MOHD YUHAZRI (scientific.net, 2012)
Performance analysis in term of identifying the system's transient response, stability and system's dynamical behavior in control system design is undeniably a must process. There are several ways in which a system can be analyzed. An example of well known techniques are using time domain and frequency domain approach. This paper is focused on the fundamental aspect of analysis of classical feedback controller in frequency domain of XY milling table ballscrew drive system. The controller used for the system is the basic PID controller using Matlab SISOTOOL graphical user interface. For this case, the frequency response function (FRF) of the system is used instead of using estimated model of transfer function to represent the real system. Result in simulation shows that after proper tuning of the controller, the system has been successfully being controlled accordingly. In addition, the result also fulfill the set requirement of frequency domain analysis in terms of the required gain and phase margin, the required maximum peak sensitivity and complimentary sensitivity function and the required stability.